PENGARUH KINERJA WIDYAISWARA TERHADAP KEPUASAN PESERTA DIKLAT DI PPPPTK TK DAN PLB - Alya Sani, - (2022)
This research is entitled "The Influence of Widyaiswara Performance on the Satisfaction of Training Participants in PPPPTK TK and PLB". The purpose of this study is to obtain an overview of the Influence of Widyaiswara Performance on the Satisfaction of Training Participants in PPPPTK TK and PLB. This study used descriptive method with a quantitative approach. Data collection techniques used questionnaires or closed questionnaires on 88 respondents. The results of the Weight Means Score (WMS) calculation with the help of Microsoft Excel 2019 and SPSS 25.0 for windows, showed that widyaiswara's performance was in the very good category, with an average score of 4,55 and the satisfaction of training participants was in the very satisfactory category, with an average score of 4,56. Based on the correlation test between the variables X and Y, a value of 0,835 was obtained and belonged to the category of "very strong" relationship levels. The results of the determination test found that variable X had an effect of 68.9% on variable Y and the rest was influenced by other factors. Then the results of the significance test obtained a value of 11,219 > 1,664 meaning that Ha was accepted, so that it could be concluded that there was a significant relationship between variable X and variable Y. Regression analysis results obtained the equation Ŷ = 8,589 + 0,834X, which means that every addition of variable X points will be followed by a change in variable Y by 0,834. The conclusion of this study, there is a positive and significant influence between Widyaiswara Performance on the Satisfaction of Training Participants in PPPPTK TK and PLB ---